The evolution of the hellenic veterinary corps - ΚΑΡΔΟΥΛΗΣ ΑΛΕΞ. Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
This is a brief review of the developing steps taken by the Veterinary Corps in the Greek Army from 1833 until 1969